Effect of car-body initial dynamic sway on overturning before high-speed trains negotiate wind speed variations. Issue 7 (3rd July 2022) - Liu, Dongrun; Zhou, Wei; Lu, Zhaijun; Gu, Houyu; Li, Tian; Zhong, Mu
Abstract : A new phenomenon has occurred during a full-scale test in which the maximum overturning coefficient did not appear at the maximum wind speed or the highest operating speed when a train negotiates wind speed variations along a section of railway. This study focused on this challenge, and conducted an experimental-numerical study of the relationship between the car-body initial dynamic sway and the operational safety during wind speed abrupt changes. The results revealed that the car-body initial dynamic-sway states (i.e., amplitude and speed) before a train passed through sections where the wind speed changed abruptly were the primary causes of this new phenomenon, and the effect of the car-body initial dynamic sway on the train's overturning safety was greater than derailment safety. Furthermore, the probability of an increase in overturning risk was greater than the probability of a decrease in risk when the train negotiated the sections where wind speed changed abruptly with different initial dynamic-sway states of the car-body. As a result, we suggested a probability critical wind speed curve for the train's ability to negotiate abrupt changes in wind speed, which provides a reference for developing a more reasonable train operation scheme in complex conditions.